Home > Resources > Homework > Math > Unit Circle

”Calculate

Answer 1

Abigail Nelson

Daniel Carter

To calculate the integral:

$ \int_{-1}^{1} \frac{1}{x + \sqrt{x^2 – 1}} dx $

First, consider the substitution $ x = \cosh(t) $, which implies $ dx = \sinh(t) dt $.

When $ x = -1 $, $ t = i \pi $ and when $ x = 1 $, $ t = 0 $:

$ \int_{i \pi}^{0} \frac{1}{\cosh(t) + \sinh(t)} \sinh(t) dt $

Knowing that $ \cosh(t) + \sinh(t) = e^t $, the integral becomes:

$ \int_{i \pi}^{0} \frac{\sinh(t)}{e^t} dt = \int_{i \pi}^{0} e^{-t} dt $

Evaluating this gives:

$ [ -e^{-t} ]_{i \pi}^{0} = -e^{0} + e^{-i \pi} = -1 + (-1) = -2 $

Answer 2

Alex Thompson

Emma Johnson

To calculate the integral:

$ int_{-1}^{1} frac{1}{x + sqrt{x^2 – 1}} dx $

First, consider the substitution $ x = cosh(t) $, which implies $ dx = sinh(t) dt $.

When $ x = -1 $, $ t = i pi $ and when $ x = 1 $, $ t = 0 $:

$ int_{i pi}^{0} frac{1}{cosh(t) + sinh(t)} sinh(t) dt $

Knowing that $ cosh(t) + sinh(t) = e^t $, the integral becomes:

$ int_{i pi}^{0} frac{sinh(t)}{e^t} dt = int_{i pi}^{0} e^{-t} dt $

Evaluating this gives:

$ [ -e^{-t} ]_{i pi}^{0} = -1 – 1 = -2 $

Answer 3

Amelia Mitchell

Michael Moore

To calculate the integral:

$ int_{-1}^{1} frac{1}{x + sqrt{x^2 – 1}} dx $

Consider the substitution $ x = cosh(t) $:

$ int_{i pi}^{0} frac{sinh(t)}{e^t} dt $

Evaluating this gives:

$ -2 $